Good Corporate Governance dan Nilai Perusahaan: Sebuah Analisis Bibliometrik - Nur Azizah, Qonita; Indrawati Yuhertiana (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The study aims to analyze the relationship between Good Corporate Governance (GCG) and the value of companies through a bibliometric approach. GCG is an important factor in improving the quality and sustainability of companies, especially in preventing economic crises and boosting investor confidence. Although GCG implementation has been a major concern, there are still gaps in its implementation in many companies, in developing countries. The study used a bibliometric analysis method with data obtained from Google Scholar, collected on January 20, 2024 using the Publish or Perish application. The data analyzed included 950 GCG-related articles and company ratings processed using VOSviewer software version 1.6.20. The results of the analysis showed a significant increase in publications related to this topic, especially in 2022, reflecting increased attention to GCG in academic research. The findings of this study confirm the importance of GCG in raising the value of the company, which in turn has a positive impact on the company's financial performance and investor confidence. The novelty of this research lies in bibliometric analysis that provides insight into the development of literature and the contribution of GCG to the value of the company, which has rarely been explored in previous research.